The Consensus of Medical Educators’ Perspectives on Patient and Public Involvement in Malaysian Medical Education - Mohamed, Abdul Rahman; Sanip, Suhaila; Omar, Mohd Rahman; Abdul Rahman, Nur Faraheen; Mohd Jamil, Mohd Ridhuan; Idris, Faridah (Penerbit Universiti Sains Malaysia, 2026)
Patient and public involvement (PPI) as ‘experts with experience’ has a significant role within the healthcare system, particularly during the pandemic when direct patient contact was limited. Thus, this study aimed to reach a consensus among Malaysian medical educators on the important characteristics and factors influencing PPI in undergraduate medical education. A Delphi study was conducted on 59 medical educators in a two-round survey using a 25-item questionnaire. Fuzzy-Delphi technique was used to analyse the results from the second-round survey. An item was accepted as a consensus if the threshold value (d) was < 0.2, the consensus percentage (c) was >75, and the fuzzy score (fs) was ≥ 0.5. The medical educators reached a consensus on 16 out of 25 items, comprising PPI activities (4 items), safety measures taken by the faculty (3 items), pressing issues (2 items), motivations for involvement (2 items), the importance of PPI (3 items), and issues with PPI during the pandemic (2 issues). Despite agreeing on most items, the discrepancies in the remaining nine items indicated the need for a cohesive framework to guide PPI in Malaysian medical education.